Some Climatic Indices for Pinot noir Maturation at a Meteorological Station in Burgundy - Bonnardot, Valerie (South African Journal of Enology and Viticulture, 2017)
This paper deals with relationships between climate and vineyard at a meteorological station in the wine-growing area of Burgundy. Statistical analyses were carried out on data for the 1975-1996 period. Climatic indices for Pinot noir grape harvests were developed for the 1975-1990 period using a composite analysis. These revealed that high spring temperatures, after a dry winter, led to an early date of Pinot noir harvest, whereas low spring temperatures, after a rainy winter, led to a late date of harvest. These indices proved to be accurate for the 1991-1996 period. The date of Pinot noir harvest could be estimated as early as May, before flowering, using these indices and linear regression methods for the 1975-1996 period. Results showed that the differences between real and estimated harvest dates were as little as five days.